2017
DOI: 10.1021/acs.jpclett.7b00536
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effects in Polymerization of Benzene under Pressure

Abstract: The enormous versatility in the properties of carbon materials depends on the content of the sp and sp covalent bonds. Under compression, if intermolecular distances cross a critical threshold, then unsaturated hydrocarbons gradually transform to saturated carbon polymers. However, the mechanism of polymerization, even for benzene, the simplest aromatic hydrocarbon, is still not understood. We used high-pressure synchrotron X-ray, neutron diffraction, and micro-Raman spectroscopy together with density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This is in agreement with the Raman active mode of the skeletal ring breathing motion. [ 34,35 ] The redshifted mode at ≈996 cm −1 in D‐B3PYMPM is about 3% smaller compared to that of H‐ B3PYMPM. In contrast to the RS spectra, Figure 1b shows that the absorption spectrum of the respective donor and acceptor chromophores does not change upon deuteration, indicating that the electron manifolds are isotope independent.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the Raman active mode of the skeletal ring breathing motion. [ 34,35 ] The redshifted mode at ≈996 cm −1 in D‐B3PYMPM is about 3% smaller compared to that of H‐ B3PYMPM. In contrast to the RS spectra, Figure 1b shows that the absorption spectrum of the respective donor and acceptor chromophores does not change upon deuteration, indicating that the electron manifolds are isotope independent.…”
Section: Figurementioning
confidence: 99%
“…It is seen that most modes are redshifted upon deuteration, since deuterium is heavier than hydrogen. [31,34,35] Specifically, the mode at ≈944 cm −1 in D-mCP is about 6% redshifted compared with that in H-mCP (1007 cm −1 ). This is in agreement with the Raman active mode of the skeletal ring breathing motion.…”
mentioning
confidence: 99%
“…For Phase I, the slope dν/dP of Raman mode at ~993 cm −1 is 5.1 cm −1 / GPa which is comparable with its earlier reported value as 5.0 cm −1 / GPa by Theiry et al [ 23 ] At higher pressure >2.5 GPa, the slope for the two Raman modes at 1004 and 1009 cm −1 are 3.1 and 3.8 cm −1 /GPa, respectively. Weizhao et al [ 34 ] observed slope of 4.32 cm −1 /GPa for pressure lower than 4.2 GPa (benzene I) and above this pressure 2.61 and 3.25 cm −1 /GPa for the two modes of benzene in Phases I and II in their static experiments. [ 34 ] Baggen et al [ 41 ] observed a phase change from benzene I to benzene II at 1.5 GPa in static experiments and observed slope of 4.6 cm −1 /GPa for lower than this pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Katrusiak et al [ 33 ] performed single crystal X‐ray diffraction studies in the pressure range 0.1 MPa to 5 GPa and in the temperature range 295 to 670 K and have determined the structure of benzene Phase II. Recently, Weizhao et al [ 34 ] used high‐pressure synchrotron X‐ray, neutron diffraction, and micro‐Raman spectroscopy together with density functional calculations to investigate the isotope effects in benzene isotopologues C 6 H 6 and C 6 D 6 up to 46.0 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…This shifts the balance of charges across the P3HT:PCBM junction and leads to lowering of V oc by 0.24 eV upon the side‐chain deuteration of P3HT . A few other recent notable examples of experimentally observed H/D isotope effects are polymerization of benzene , stability of organic molecules in the electronic beam of the transmission electron microscope and the spin response in polymer films and devices . It is even argued that olfaction is sensitive to the H/D isotopic substitution through its effect on noncovalent interactions between the molecules .…”
Section: Introductionmentioning
confidence: 99%